Engine-driven synchronous generators: design considerations for grid code compliance - Narayanan, Sridhar (2019)
This thesis aims to provide a set of design criteria for designing synchronous generators (SGs) for engine driven generating sets to meet the emerging grid code requirements. Historically, central plants have been an integral part of the electric grid, in which the power generation facilities are typically located closer to the resources or further away from the loads. Liberalization of the energy market in the early parts of the 21st century combined with stringent environmental policies and emission regulation have forced electrical energy providers to opt for renewable sources and distributed generation. While both these methods of power generation offer better efficiency and economies of scale compared to large power plants, they introduce instability in the grid. To ensure stable supply of electrical power to consumers, many transmission and distribution system operators are enforcing performance expectations on power plants connected to the grid – Grid Codes. These regulations pose great design challenges to the manufacturers and designers of generating sets and associated components, especially synchronous generator (SG) manufacturers. In this work, relevant grid codes are analyzed and specific requirements are defined. A practical and quick analysis method is developed and then used to simulate engine driven SGs connected to electric grid. A neural network based simplification is applied to minimize the number of simulations required to provide guidelines for designing SGs for grid code compliance. Low Voltage Ride Through tests are performed to validate the proposed guidelines. The effects of system solutions on the design parameters are also briefly analyzed. The proposed design criteria are applied to SGs and are validated through grid code certification tests. As vessel to prove the validity of the concepts mentioned above, a 1400 KVA alternator is prototyped and experimental measurements are finally performed. The work presented in the thesis has led to a comprehensive understanding of grid codes and their effect on design and selection of engine driven SGs is obtained and a granted patent on a novel retrofit-able method to reduce fault currents in a SG.